2007
DOI: 10.1016/j.physb.2007.08.192
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of defects in pulsed-laser deposition grown ZnO with levels at 300 and 370meV below the conduction band

Abstract: We have used deep level transient spectroscopy (DLTS) to characterize defects in ZnO grown by pulsed-laser deposition (PLD). Using high resolution Laplace DLTS, we found that at the high temperature side of the commonly observed defect E3 (about 300 meV below the conduction band) another close lying peak (E3′ with thermal activation energy of 370 meV) is also observed. The concentration ratio of E3 and E3′ depends on the annealing history of the samples. It is most prevalent in as-grown samples and samples tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 11 publications
8
28
0
Order By: Relevance
“…26 In addition to the commonly observed trap E 3 ͑0.3 eV͒, another close lying peak E 3 Ј ͑0.37 eV͒ was observed by using high resolution Laplace-transform DLTS in ZnO grown by pulsed-laser deposition. 27 An increase in the concentration of E 3 Ј after annealing in oxygen suggested that the trap could be associated with O. In that study, however, E 3 Ј was not found in a bulk ZnO grown by the vaporphase technique ͑serving as a reference͒.…”
Section: Resultsmentioning
confidence: 72%
“…26 In addition to the commonly observed trap E 3 ͑0.3 eV͒, another close lying peak E 3 Ј ͑0.37 eV͒ was observed by using high resolution Laplace-transform DLTS in ZnO grown by pulsed-laser deposition. 27 An increase in the concentration of E 3 Ј after annealing in oxygen suggested that the trap could be associated with O. In that study, however, E 3 Ј was not found in a bulk ZnO grown by the vaporphase technique ͑serving as a reference͒.…”
Section: Resultsmentioning
confidence: 72%
“…However, in addition to the commonly observed trap E3 ͑0.3 eV͒, another close lying peak E3Ј ͑0.37 eV͒ was reported by using high resolution Laplace-transform DLTS in ZnO grown by pulsed-laser deposition. 11 An increase in the concentration of E3Ј after annealing in oxygen suggested that this new trap could be associated with oxygen incorporation. In that study, however, E3Ј was not found in any bulk-grown ZnO ͑serving as a reference͒.…”
Section: Observation Of Surface Traps On Zn Facementioning
confidence: 99%
“…In the literature, defects in ZnO (single crystal or sputtered lm) with similar energy values have been observed in DLTS and impedance spectroscopy. [52][53][54][55][56] Ref. 53 suggests that these defects might relate to the incorporation of oxygen in the crystal lattice.…”
Section: 49mentioning
confidence: 99%
“…[52][53][54][55][56] Ref. 53 suggests that these defects might relate to the incorporation of oxygen in the crystal lattice. We emphasize that the origin of defects in ZnO is generally under debate in the literature [52][53][54][55][56][57][58] and that a direct comparison with the literature needs to be done with caution, as the defect density is sensitively affected by the growth method and annealing conditions.…”
Section: 49mentioning
confidence: 99%